CHARACTERIZATION OF GHFHY3/FAR1 GENE FAMILY MEMBERS IN UPLAND COT-TON (G.HIRSUTUM L.) (Scientific journal of the Fergana State University, 2026)
Light is one of the critical environmental factors influencing plant growth. In plants, light response is mainly regulated by three types of photoreceptor genes: phytochromes, cryptochromes, and UV-B photoreceptors. Among these groups, phytochromes play a particularly important role. These receptors perceive red and far-red light and subsequently regulate numerous downstream transcription factors either directly or indirectly, thereby influencing seed germination, stem elongation, leaf expansion, flowering, and early maturation processes.The downstream transcription factors include members of the FAR1-RELATED SEQUENCE1 (FAR1) and FAR-RED ELONGATED HYPOCOTYL3 (FHY3) gene family (FHY3/FAR1), which are believed to have originated from transposases. Members of the FHY3/FAR1 gene family have been studied in various crop species, and their amino acid sequences have been characterized in detail.In this study, we analyzed the amino acid sequences of FHY3/FAR1 gene family members present in the genome of upland cotton (Gossypium hirsutum L.). Their individual characteristics—including coding DNA sequences (CDS), amino acid sequences, subcellular localization, and physiological and biochemical properties—were identified and described.